Presence of Celleporaria brunnea (Bryozoa: Lepraliellidae) in the Central Mediterranean: first occurrence in the Gulf of Taranto. (15th September 2015) - Lezzi, Marco; Pierri, Cataldo; Cardone, Frine
Abstract : We report the presence of the non-indigenous species (NIS) Celleporaria brunnea (Bryozoa, Ascophora) in the Central Mediterranean. It was found in the Gulf of Taranto (Ionian Sea, southern Italy), which represents one of the most important hotspots for NIS in the Mediterranean. Using PVC plates as species collectors, immersed in different times of the year, we observed a recruitment of C. brunnea during the warmer period of the year from July to October. This work highlights a range expansion of C. brunnea and provides information about its autoecology traits in the host environment.